EARLY DETECTION AND DIAGNOSIS OF THYROID CANCER BASED ON AN ARTIFICIAL INTELLIGENCE MODEL (International journal of artificial intelligence, 2025)
Background: Thyroid cancer is the most prevalent endocrine malignancy, and its incidence has increased significantly worldwide over the past two decades. Early detection and accurate diagnosis play a critical role in improving treatment outcomes and survival rates.Objective: This study aims to develop and evaluate an artificial intelligence (AI)-based model for the early detection and diagnosis of thyroid cancer using clinical, imaging, and cytological data.Methods: A dataset of 1,200 thyroid patients (740 benign, 460 malignant) collected between 2018 and 2023 from three tertiary hospitals was analyzed. Key features included demographic data, thyroid function tests, ultrasound parameters, and fine-needle aspiration (FNA) cytology reports. Several machine learning algorithms—logistic regression, random forest, and convolutional neural networks (CNNs)—were trained and validated. Model performance was assessed using sensitivity, specificity, accuracy, and area under the ROC curve (AUC).Results: The CNN model achieved the best diagnostic accuracy (94.6%), with a sensitivity of 92.3% and specificity of 96.1%, outperforming conventional models. The AI system demonstrated reliable differentiation between benign and malignant nodules using ultrasound and cytology images.Conclusion: The proposed AI model provides a promising non-invasive tool for early thyroid cancer detection and diagnostic support. Integration of AI systems into routine endocrinological practice can improve clinical decision-making and reduce diagnostic errors.